Peculiarities of Seeking Psychological Help Among Students from Russia and Uganda - Nsubuga, Moses (Tazkiya Journal of Psychology, 2024)
The study examines attitudes toward getting professional mental health assistance among Russian and Ugandan university students, and it finds notable disparities that are driven by developmental and cultural factors. The following instruments were used in the methodology; to measure the attitudes towards seeking psychological help, the Inventory of Attitudes toward Seeking Mental Health Services (IASMSH) was used; and the Carol D. Ryff psychological well-being scale was used to measure psychological wellbeing.  The results show that attitudes toward therapy, social support, psychological well-being, and emotional openness are all statistically significantly correlated with one other. Interestingly, when it comes to getting psychological assistance, Russian students are more positive than their Ugandan counterparts. Both cohorts have a low use of mental health services, frequently resorting to campus health centres for physical symptoms associated with stress. It is essential to comprehend these elements in order to improve student referral rates and counselling services.